Structural Colours Based on Basic Structuration Theory of Photonic Crystals (Journal of Fiber Bioengineering and Informatics, 2019)
With the rapid development of photonic crystals (PCs), PC structural colouration has gained greatattention from many more researchers. Dyeing methods can benefit a lot from PC structural colours andbecome more environmentally friendly. This modified colouration is superior to the traditional ordinaryand chemical dyes and pigments, because of the special characteristics of PC structural colours, such ashigh brightness, high saturation, never fading, iridescent effect, polarization phenomenon, and so on. Inthis work, the concept and clarification of PCs, the PC structural colour, the mechanism of structuralcolouration and various methods of preparing artificial PC are reviewed. Generally, PC can be dividedinto different types because of diverse spatial distribution characteristics of the photonic band gap. Thebasic principle of the structural colouration is explained in detail. In the process of producing structuralcolour, it is of great importance to synthesize silica nanoparticles by solvent change technique (SVT)and self-assembly gravity sedimentation method is described minutely in this paper. Meanwhile, thestrengths and weakness of these methods are compared to select the best method for manufacturingstructural colours. The applications of PC structural colour are summarized, and some problems areproposed which need to be solved in PC development in the future.
Keywords: Photonic Crystals; Structural Colour; Nano-particles; Structuration Theory; Solvent Varying Technique; Self-assembly; Gravity Sedimentation